Learning Arduino as a Simple River Water Level Detection System Based on Ultrasonic Sensors - Bertha Anggita Purwandani; Dimitra Ega Lianny; Melani Fitri Anggraeni; Putri Fauziah; Nugroho Adi Pramono; Rahmat Hartawan (Journal of Disruptive Learning Innovation (JODLI), 2021)
Current technological advancements are rapidly and impact daily life. Developing technology can be applied in many programs, one of which is as a tool for education. As shown in this study, technology as a mode of learning can be implemented in daily life. This study examined Arduino programming to create a river water level detection system using an ultrasonic sensor. This research is expected to be used as a learning tool for using Arduino as a microcontroller and can be applied in daily life. Additionally, by developing this river water level detection system, it will be possible to mitigate flood disasters.